A report on occurrence of Phlebotomine sand flies (Diptera: Psychodidae) and two new country records from Andaman & Nicobar Islands, a Union territory of India - Jambulingam, P.; Srinivasan, R.; Gopalakrishnan, S. (Zootaxa, 2022)
A cross-sectional survey was carried out to determine sand fly fauna of the Andaman and Nicobar Islands that are known for tourist attraction from different countries, due to their scenic beauty. The study area includes 40 localities, stretching from south and middle to north Andaman Islands. Sand fly collections were made from day time resting shelters such as human dwellings, cattle-shed, and bushes in fringe of villages. A total of 1055 sand flies, comprising of six species were collected. Se. (Neo.) barraudi was found to be the predominant species, comprising of 57.7% of the total. Other species found to occur were Se. (Par.) babu (27. 4%), Se. (bailyi) 8. 1%, Se. (Neo.) gemmea (4. 9%), Se. (Neo.) quatei (2. 1%) and Phlebotomus (Ana.) stantoni (0.3%). Se. (Neo.) gemmea is reported to be a vector transmitting visceral leishmaniasis and dermal leishmaniasis in southern Thailand. Se. (Neo.) gemmea and Se (Neo.) quatei are new country records adding to the existing list of sand fly fauna of India. This is the first report on sand flies from Andaman and Nicobar Islands.